2020
DOI: 10.1155/2020/4501261
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction Conditions of Phytochemical Compounds and Anti‐Gout Activity of Euphorbia hirta L. (Ara Tanah) Using Response Surface Methodology and Liquid Chromatography‐Mass Spectrometry (LC‐MS) Analysis

Abstract: Gout is a common disease affected most of the people due to the elevation of uric acid in the blood. Flavonoid and phenolic compounds are reported to exert the anti-gout activity of medicinal plants. Hence, this study aimed at optimizing the extraction conditions of phenolic and flavonoid compounds as well as the anti-gout (xanthine oxidase inhibitory activity) in vitro of Euphorbia hirta using response surface methodology (RSM). The plant part used was the whole plant excluding roots. The effects of three ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…In order to obtain the most sensitive ionization effect for analytes, positive and negative ion modes were investigated at different collision energy (CE) to optimize the signals and obtain maximal structure information from the ions for the mass range of 100–3200 m/z. Data processing was performed by Mass Hunter Qualitative Analysis software and peak identification was carried out based on comparison with literature values and online database [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…In order to obtain the most sensitive ionization effect for analytes, positive and negative ion modes were investigated at different collision energy (CE) to optimize the signals and obtain maximal structure information from the ions for the mass range of 100–3200 m/z. Data processing was performed by Mass Hunter Qualitative Analysis software and peak identification was carried out based on comparison with literature values and online database [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…At a fixed extraction temperature of 51 °C, as the extraction time decreased and the liquid-to-solid ratio increased, the TFC yield increased. Abu Bakar et al (2020) and Sheng et al (2013) reported the same pattern as the TFC steadily increased as the liquid-to-solid ratio increased. This could be because of the increase in the driving force for the mass transfer of the TFC, which led to the high TFC recorded after the analysis (Liu et al 2010).…”
Section: The Effect Of the Extraction Variables On The Tfcmentioning
confidence: 61%
“…Single-factor analysis. To determine a suitable range of factors, single-factor analysis was conducted using solvent concentration (20,40,60,80 and 96% v/v), time for extraction (60,120,180,240, and 300 minutes), extraction temperature (25,35,45,55, and 65°C), pH (2.5, 5.5, 7, 9, and 12), and solid-liquid ratio (1:10, 1:20, 1:30, 1:40, and 1:50 g/mL). One independent variable was varied according to the set range whilst keeping the others constant.…”
Section: Experimental Designmentioning
confidence: 99%
“…It is therefore imperative to assess the interaction between the independent variables. One of the appropriate techniques is to use the response surface method (RSM) as a tool to optimize the factors that affect extraction efficacy as well as to obtain maximum recovery of the compounds of interest [23][24][25] . The central-composite-design (CCD) of the response-surface-method is known to be useful for the optimization of extraction parameters of bioactive compounds 26 .…”
Section: Introductionmentioning
confidence: 99%